Effect of Modified Eggshell on Adsorption Capacity of Chromium(VI) from Aqueous Solution - Alomari, Abdulaziz Ali (Asian Journal of Chemistry, 2020)
The aim of this work is to investigate the use of eggshell for adsorption of Cr(VI) from aqueous solution and the effect of thermal treatment as well as coating with Fe2O3 of eggshell on the extraction percent of Cr(VI). The XRD, FTIR and SEM techniques proved that the eggshell mainly composed of calcite rhombohedral structure in addition to a trace of quartz silica residual protein fibers. Heating at 550 ºC does not decompose eggshell but decomposes the residual protein. The effect of pH, weight of eggshell adsorbent, contact time, and initial concentration of Cr(VI) ions on the adsorption of Cr(VI) on eggshell sorbents were determined under static conditions by the batch equilibrium technique. The sorption kinetic as well as mechanistic isotherm parameters of Cr(VI) on the eggshell sorbent, were analyzed. It was concluded that the adsorption of Cr(VI) on eggshell increases as pH increases in the range 3-7, then, with decreases at higher pH. The extraction percent of Cr(VI) increases with an increase in the dosage of eggshell sorbents. The optimum dosage of eggshell adsorbents was found to be 5 g after which the extraction percent of Cr(VI) did not marked increase. The extraction percent of Cr(VI) by eggshell sorbents rapidly increases within 60 min followed by a slower extraction after that when maximum adsorption was reported. The adsorption capacity of Cr(VI) ions is slightly reduced in case of heated eggshell due to the change that occurs in the pore size distribution and structure of eggshell during heating. Hence, the thermal treatment and coating with Fe2O3 do not affect the chemical structure of eggshell sorbents. The adsorption kinetics data were best fitted with the pseudo-second-order equation and the adsorption isotherms were best fitted with the Langmuir isotherm model.